EXPLORING THE DYNAMICS OF FOREIGN LANGUAGE EDUCATION WITHIN SOCIO-CULTURAL TRANSFORMATIONS: A COMPREHENSIVE ANALYSIS - Nykyporets, Svitlana (Collection of scientific papers «ΛΌГOΣ», 2023)
In a world marked by rapid socio-cultural transformations, foreign language education assumes a pivotal role in equipping individuals with the skills needed to navigate the complexities of an interconnected global society. This article presents a comprehensive examination of foreign language education within the dynamic context of socio-cultural change. Firstly, it emphasizes the imperative of dynamic pedagogical strategies, stressing that traditional teaching approaches are no longer sufficient. Secondly, the article underscores the significance of assessing language policies’ practical impact. Data-driven approaches are crucial for policymakers to gauge the effectiveness of language policies and make informed decisions in resource allocation and policy adjustments. Thirdly, the study explores the promising potential of emerging technologies, such as virtual reality, AI-driven language assistants, and mobile apps, in enhancing language acquisition and intercultural competence. However, effective integration demands further research to ensure accessibility, affordability, and pedagogical soundness. Lastly, a cross-disciplinary approach synthesizes insights from linguistics, education, and cultural studies, enriching our understanding of foreign language education’s role. It encourages scholars and educators to collaborate across disciplinary boundaries, fostering a more comprehensive perspective. These findings and prospects collectively offer a roadmap for educators, policymakers, and researchers to advance foreign language education in a world characterized by continual socio-cultural transformations.